Information Access by Research Scholars in R.M.K. Engineering College Library: A Study - P. Krishnamoorthy; Muthusamy, C. (Indian Journal of Information Sources and Services, 2018)
This study is an investigation of Information access by Research Scholars in Engineering College Libraries with special reference to R.M.K. Engineering College Library, Tiruvallur District, Tamil Nadu. 58 questionnaires were distributed among research scholars of R.M.K. Engineering College to collect relevant data. 94.83% (55) research scholars responded where 23 (41.82%) visit the library once in a week, 17 (30.91%) visit Twice a week, 10 (18.18%) respondents visit daily, 5 (9.09%) visit fortnightly. It is found that 85.44% opined that the working hours of their respective libraries is convenient and only 14.56% researchers opined not convenient and majority of the research scholars 96.36% visit the Library to use E- journals and 50.91% researchers visit the Library for audio visual resources. Library is playing vital role to meet multidimensional demands of staff, students and research scholar for information and knowledge.